S–V Semantic Affinity in Presentation Sentences with Preverbal Rhematic Subject - Martin Adam (ELOPE, 2013)
Firmly anchored in the Praguian theory of functional sentence perspective (FSP), the present paper discusses the prototypical type of sentences implementing the so–called Presentation Scale (i.e., that containing a rhematic subject in preverbal position) within fiction narrative discourse. Special attention is paid to the semantic affinity operating between the subject and the predicate; in such distributional fields (cf. A bird chirped on the twig) the verbs seem to semantically support the character of their subjects. Thus, the S–V affinity appears to play a significant role in enabling the English verb to express existence or appearance on the scene in an implicit way. The phenomenon of semantic affinity is discussed on the basis of FSP investigation of a sample corpus of narrative texts compiled and processed by the author. Apart from the syntactic–semantic analysis, S–V affinity is also examined through the prism of eminent Czech representatives of the Prague School legacy, such as Vilém Mathesius, Jan Firbas, Aleš Svoboda and Libuše Dušková.